PENGARUH PEMBIAYAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DAN SARANA PRASARAN PENDIDIKAN TERHADAP MUTU PEMBELAJARAN (PENELITIAN DI SMA MUHAMMADIYAH KABUPATEN BANDUNG) - Wildan Al-Ghofiqi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
The purpose of this study was to identify the effect of School Operational Assistance (BOS) funding and educational infrastructure on the quality of learning in SMA Muhammadiyah Bandung Regency. This research was conducted using a quantitative approach with a descriptive correlational quantitative method. Then it was analyzed statistically using the steps of validity, data normality, linear regression and correlation using SPSS v.28.0. The results of this study. This study uses the Simultaneous F-Test, which means testing the effect of the X variable together on the Y variable. The basis for decision making, if the value of Sig > 0.05, then Ho is accepted. However, if the value of Sig < 0.05 then Ho is rejected. The Sig value for Regression is 0.009 b this value is smaller than 0.05, then Ho is rejected. The R Squere value of this study is 0.153 or 15.3%. So it can be said that the Financing of School Operational Assistance (BOS) funds and educational infrastructure together gives the remaining 15.3% effect (100% - 15.3% = 84.7%) is influenced by other factors such as cleanliness of the heart, perseverance and understanding of goals